Divergent prevalence of Warthin tumor in Africa and Asia: A consequence of variation in smoking index? - Ogechukwu Okoye, Jude (Annals of Medical Research, 2021)
Aim: This study assessed the prevalence of WT in Africa and Asia as it relates to smoking index and malignant tumors of the parotid gland. Materials and Methods: Peer-reviewed articles found on Google Scholar, Scopus, EMBASE, Web of Science, and PubMed Central were systematically reviewed. Results: Significant higher prevalence of WT and smoking index (intensity and prevalence of smoking) were observed in Asia than in Africa (p= 0.003 and p=0.001, respectively). A significant direct relationship was observed between the frequency of WT and smoking index (p= 0.001) while a significant inverse relationship between the prevalence of WT and malignant tumors of the parotid gland (p= 0.039) was also observed. In Africa, South Africa and Morocco had the highest prevalence of WT (13.4% and 11.5%, respectively) while Tanzania and Nigeria had the lowest prevalence of WT (3.6% and 0.0%, respectively). In Asia, Taiwan and South Korea had the highest prevalence of WT (46.6% and 38.8%, respectively) while Iran and Pakistan had the lowest prevalence of WT (7.6% and 3.5%, respectively). Conclusion: This review revealed that the high prevalence of WT in Asia could be due to a high smoking index in the continent. It suggests that the incidence of WT could be used as an alternative tool for monitoring the effect of smoking across countries.
Keywords: Africa; Asia; smoking index; Turkey; warthin tumor